Gamification and Sugar: A School-Based Pilot Study of Social Marketing and Gamification Approaches to Reduce Sugary Drink Intake in Pasifika School Students. (September 2021) - Sundborn, Gerhard; Thornley, Simon; Grey, Corina; Gentles, Dudley; Jackson, Rod T.; Swinburn, Boyd; Veatupu, Loma; Lang, Bodo
The aim of this study was to investigate a social marketing–gamification intervention to reduce sugary drink intake drawing on popular culture of Pasifika secondary school students in Auckland, New Zealand. Students aged 11 to 14 years from one coeducational high school participated in the 11-week pilot study. The 9-week intervention was undertaken in assemblies and classrooms. Baseline and follow-up measures were completed by 227 and 220 students, respectively, of 298 enrolled students. Retention of the "3-6-9" teaching related to maximum daily sugar intake increased from 9% at baseline to 97% at follow-up ( P < .0001). Significant increases were observed of students who correctly answered sugar content of drinks. Overall consumption of sugary drink decreased at follow-up by 0.46 glasses per day. The main conclusion from this study was that this school-based gamification educational package to convey messages about sugar content of drinks using popular modes of engagement is a promising intervention that was acceptable and well supported by school staff and students.